Fuel cell catalyst layer evaluation using a gas diffusion electrode half-cell: Oxygen reduction reaction on Fe-N-C in alkaline media - Ehelebe, Konrad; Ashraf, Talal; Hager, Simon; Seeberger, Dominik; Thiele, Simon; Cherevko, Serhiy (Electrochemistry Communications, 2020)
Anion exchange membrane fuel cells (AEMFC) are a promising technology to allow the application of non-precious metal catalysts. While many of such catalysts have been identified in numerous recent fundamental research studies, reports evaluating these catalysts in realistic AEMFC catalyst layers together with stability assessments are rare. In the present work we show that fast and reliable evaluation and optimization of Fe-N-C-based oxygen reduction reaction (ORR) catalyst layers can be achieved using a gas diffusion electrode (GDE) half-cell approach. To set a benchmark in such measurements, a commercial Pajarito Powder Fe-N-C catalyst and commercial AemionTM ionomer are used. It is demonstrated that the ORR performance can be increased significantly by fine-tuning of the ionomer activation time. Furthermore, the optimized Fe-N-C-based catalyst layer shows very high stability with no observable performance deterioration after 5000 cycles in the 0.6–1.0 V vs. RHE potential window.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Alkaline fuel cell; Alkaline ionomer; Fe-N-C; Gas diffusion electrode; Non-noble metal catalyst; Oxygen reduction reaction